Updating Algerian solar atlas using MEERA-2 data source - Kamel Abdeladim; Abdelhak Razagui; Smail Semaoui; Amar Hadj Arab (Energy Reports, 2020)
According to its geographical location, Algeria holds one of the highest solar potential in the Mediterranean basin, as indicated in many studies. Unfortunately, an important lack of data of the solar global radiation is observed. With a huge area of 2 381 741 km2, it is necessary to have numerous stations performing radiation measurement in order to quantify in an objective way the solar potential. Previously, several studies have been conducted dealing with solar potential evaluation. In this study, an update of the Algerian solar atlas is presented. Thus, a solar mapping on the national territory was carried out based this time on data measured over a period of almost 37 years. In fact MEERA-2 "The Modern-Era Retrospective Analysis for Research and Applications, Version 2, NASA", were used in this study. Therefore, solar maps for solar radiation on different tilting planes were plotted thanks to the use of SURFER® software, through Kriging interpolation method. Furthermore, measured data for five (05) locations across the country were used in order to make comparison to those given by MERRA-2.
Keywords: 330; Kriging interpolation method; MEERA-2 data; Solar atlas; Solar radiation; SURFER®software